Is antibacterial treatment intensity lower in elderly patients?: a retrospective cohort study in a German surgical intensive care unit - Beier, Dominik; Weiß, Christel; Hagmann, Michael; Balaban, Ümniye; Thiel, Manfred; Schneider-Lindner, Verena (BMC health services research, 2019)
Demographic change concurrent with medical progress leads to an increasing number of elderly patients in intensive care units (ICUs). Antibacterial treatment is an important, often life-saving, aspect of intensive care but burdened by the associated antimicrobial resistance risk. Elderly patients are simultaneously at greater risk of infections and may be more restrictively treated because, generally, treatment intensity declines with age. We therefore described utilization of antibacterials in ICU patients older and younger than 80 years and examined differences in the intensity of antibacterial therapy between both groups.
Gesehen am 01.10.2019